Rejoso Kita: Save Water, Preserve Life - World Agroforestry Centre (World Agroforestry Centre, 2020)
The Rejoso Watershed provides vital livelihoods for the communities in 16 sub-districts in the eastern part of Pasuruan District, East Java Province. The watershed strategically functions as the source of clean water for Pasuruan City and its surrounding areas, such as Sidoarjo and Gresik districts, and Surabaya City; the latter the metropolitan capital of East Java and the second-largest such area in Indonesia.